Das System der Erde - was bewegt die Welt? Lebensraum und Zukunftsperspektiven - Reitner, Joachim; Karg, Ute (Universitèatsverlag Gèottingen, 2005)
Our planet earth is a system - scarcely understood - of geological, biological und cosmic processes of great variety, which make it an interesting object of research. The papers listed here deal with topics of a series of lectures open to the public, presented at the Academy of Sciences and at the Georg August University of Gèottingen, which were organised by the publishers of this book. It is the publishers' aim to bring before the public a few important and interesting geoscientific aspects. Needless to say, there is no claim to cover all aspects of this subject area. However, the publishers would like to initiate readers to concentrate more deeply on scientific topics. The selected material should help them to find their way through the diversity of this branch of research.